Identity and Language Learning: Extending the Conversation - Norton, Bonny (Channel View Publications, 2013)
Identity and Language Learning draws on a longitudinal case study of immigrant women in Canada to develop new ideas about identity, investment, and imagined communities in the field of language learning and teaching. Bonny Norton demonstrates that a poststructuralist conception of identity as multiple, a site of struggle, and subject to change across time and place is highly productive for understanding language learning. Her sociological construct of investment is an important complement to psychological theories of motivation. The implications for language teaching and teacher education are profound. Now including a new, comprehensive Introduction as well as an Afterword by Claire Kramsch, this second edition addresses the following central questions:- Under what conditions do language learners speak, listen, read and write?- How are relations of power implicated in the negotiation of identity?- How can teachers address the investments and imagined identities of learners?The book integrates research, theory, and classroom practice, and is essential reading for students, teachers and researchers in the fields of language learning and teaching, TESOL, applied linguistics and literacy.This book is open access under a CC BY ND licence.